1923 N.M. Laws 179, § 2 - (:unkn) unknown (My University, 1923)
Ch. 115, § 2: Provided that the use of explosives to destroy any building, structure, or train, or to injure or scare any human being constitutes a felony
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME